Do we have today a reliable method to detect the moment of loss of consciousness during induction of general anaesthesia? - Ferreira, Ana Isabel Leitão (2020)
This review aims to give an overview of the current state of monitoring depth of anaesthesia and detecting the moment of loss of consciousness, from the first clinical signs involved in anaesthesia to the latest technologies used in this area. Such techniques are extremely important for the development of automatic systems for anaesthesia control, including preventing intraoperative awareness episodes and overdoses. A search in the databases Pubmed and IEEE Xplore was performed using terms such anaesthetic monitoring, depth of anaesthesia, loss of consciousness, as well as anaesthesia indexes, namely BIS. Despite the several methods capable of monitoring the hypnotic state of anaesthesia, there is still no methodology to accurate detect the moment of loss of consciousness during induction of general anaesthesia.